A meta-analysis of pharmacological treatments for preventing acute renal injury after juvenile heart surgery. (December 2022) - Saeed, Haitham; Abdelrahim, Mohamed E.A.
Abstract: Background: Children who have had heart surgery frequently develop an acute renal injury, which complicates postoperative care and is associated with a high mortality rate. Several pharmacological interventions are introduced for preventing postoperative renal dysfunction. Aim of review: The current meta-analysis aims to evaluate the effectiveness of pharmacological interventions in preventing postoperative renal dysfunction after congenital heart surgery in pediatric subjects. Key scientific concepts of review: A systematic literature search up to July 2021 was performed and 20 studies included 2612 subjects with congenital heart surgery at the start of the study; 1527 of them were administered pharmacological interventions and 1070 were placebo. The odds ratio (OR) with 95 % confidence intervals (CIs) was calculated to assess the effects of pharmacological interventions compared to placebo on preventing postoperative renal dysfunction after congenital heart surgery in pediatric subjects using the dichotomous method with a random or fixed-effect model. Pharmacological interventions had significantly lower postoperative renal dysfunction after congenital heart surgery in pediatric subjects when using dexmedetomidine (OR, 0.44; 95 % CI, 0.28–0.68, p  < 0.001), and compared to placebo. However, pharmacological interventions had no significant effect on postoperative renal dysfunction after congenital heart surgery in pediatric subjects when using corticosteroids (OR, 0.86; 95 % CI, 0.60–1.25, p  = 0.44), fenoldopam (OR, 0.47; 95 % CI, 0.22–1.02, p  = 0.06), and aminophylline (OR, 0.72; 95 % CI, 0.22–2.33, p  = 0.58) compared to placebo. Dexmedetomidine may reduce postoperative renal impairment after congenital heart surgery in children compared to placebo. Pediatric corticosteroids, fenoldopam, and aminophylline did not affect postoperative renal impairment after congenital heart surgery compared to placebo. Additional research is needed to confirm these results. Highlights: We performed a meta-analysis to evaluate the effectiveness of pharmacological interventions in preventing postoperative renal dysfunction after congenital heart surgery in pediatric subjects. Dexmedetomidine may lower the risk of postoperative renal dysfunction after congenital heart surgery in pediatric subjects compared to placebo. However, pharmacological interventions had no significant effect on postoperative renal dysfunction after congenital heart surgery in pediatric subjects when using corticosteroids, fenoldopam, and aminophylline compared to placebo. Furthers studies are required to validate these findings.